2a-6=9(a+1)+12a+5

Simple and best practice solution for 2a-6=9(a+1)+12a+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2a-6=9(a+1)+12a+5 equation:



2a-6=9(a+1)+12a+5
We move all terms to the left:
2a-6-(9(a+1)+12a+5)=0
We calculate terms in parentheses: -(9(a+1)+12a+5), so:
9(a+1)+12a+5
We add all the numbers together, and all the variables
12a+9(a+1)+5
We multiply parentheses
12a+9a+9+5
We add all the numbers together, and all the variables
21a+14
Back to the equation:
-(21a+14)
We get rid of parentheses
2a-21a-14-6=0
We add all the numbers together, and all the variables
-19a-20=0
We move all terms containing a to the left, all other terms to the right
-19a=20
a=20/-19
a=-1+1/19

See similar equations:

| 2x-86=x-18 | | 4m^2+7m-36=0 | | –6+7q=6 | | –6+7q=6q | | 4(x-7)-2=-30 | | 60+.65x=3,390 | | 7x+24=19x+33 | | 4(x+7)-2=-30 | | 2x-5+4x-18=25 | | -7(x+5)=-5(x-3) | | -5t-14t=-19 | | 4(3x+1)−7x=6+5x−2 | | 16.2=20/n | | 7g-3g-1=11 | | 7k+15=120 | | 18+7w=-10-5+10w | | 5x​ +12=2 | | 3t+7t=36 | | e-4/15-e/10=1. | | 3n-6=-60 | | -3x-11+20=-22 | | 14v=-18+16v | | 19-13p=-17-7 | | 4(3x+8)=-17+25 | | x^2+5x=644 | | -5-19z=-15z+19 | | 4w+15=‐13 | | 5x-2x+5=7 | | 2x+17=8x-11 | | 6x+1=2x=5 | | 3(3g+2)=5(2g–1) | | e-4/15-e/10=1 |

Equations solver categories